BAHASA TETUN, DAWAN, DAN ROTE DI NUSA TENGGARA TIMUR (KAJIAN KOMPARATIF DAN BUDAYA) - , EMI RENOAT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the relation of Tetum kinship, Dawan and Rote which is administratively located in Belu district, Middle East District(TTS) South, and Rote- Ndaoregency of East Nusa Tenggara province. Study of kinship relations of the third language, is done through the corner of synchronic and diachronic study with quantitative and qualitative approaches. Quantitative approaches aimed to find out the kinship relations using of the third languages by lexicostatistics techniques. Meanwhile, a qualitative approach aimed to find out the evidence of the third language kinship relations in the field of phonological and lexicon, through shared innovation criteria. In addition synchronic and diachronic study, this research is also involves the study of culture Ttn, Dwn, and Rt to prove the results of diachronic study. Results synchronic study of the third languages show a close kinship. Ttn language has consonant clusters /kw/, /ks/, and /kl/